Integration of Corporate Governance, Risk Management, and Financial Digitalization: Its Impact on Banking Company Performance and Value - Aminudin Aminudin; Hari Gursida; Yohanes Indrayono (Riviera Publishing, 2025)
This study aims to analyze the influence of the integration of corporate governance, risk management, and financial digitalization on the performance and value of banking companies in Indonesia. The research population includes foreign banks, government banks, and private banks classified as KBMI 3 and KBMI 4 for the 2019–2024 period. The research method used is explanatory with a quantitative approach. Data was obtained from annual reports, sustainability reports, and publications by the Financial Services Authority (OJK) and Bank Indonesia. Data analysis was carried out using Structural Equation Modeling (SEM-PLS). The results of the study show that corporate governance and risk management have a significant effect on company performance, while financial digitalization has a mediating role in increasing company value through increased operational efficiency and transparency. These findings affirm the importance of integrating governance, risk, and digitalization strategies in the face of the era of technology-based finance.